A Critical Review on Phytochemical Profile and Biological Effects of Turnip (Brassica rapa L.) - Cao, Qingsui; Wang, Ge; Peng, Ye (Frontiers in Nutrition, 2021)
A growing number of medicinal and edible plants have attracted extensive attention due to their abundant constituents and biological activities including turnip. Turnip (Brassica Rapa L.) is an herbaceous biennial plant belonging to Cruciferae Brassica. As one of the oldest cultivated vegetables widely consumed in Asia, turnip has received significant attention on the studies of its bioactive components and biological function. Multiple bioactive components in turnip, such as glucosinolates, isothiocyanate, phenolic compounds, flavonoids, and organic acids, were identified. The bioactivity studies on turnip revealed its anticancer, antimicrobe, anti-diabetes, anti-hypoxia, anti-oxidation, and nephroprotective activity. The present review mainly summarized the previous studies on chemical compositions of turnip and the bioactivities associated with turnip. Further studies on the extraction and purification of compounds from turnip as well as its potential molecular mechanisms are highly needed to utilize turnip as a functional food plant in a better way.